INVESTIGATION OF MECHANICAL AND ELASTIC STRESSES IN ANSYS PROGRAM BY FINITE ELEMENTS METHOD OF 3D LATTICE ROOF MODEL - Taşkaya, Semih (My University, 2018)
In this study, the lattice roof model was designed in 3 dimensions using the finite element method in the Ansys packageprogram. This method can be understood by making the complex engineering applications is a method to provide thesolution can be controlled by the system. The element type of the model, the outside diameter of the truss pipe, the thicknessof the meat, the modulus of elasticity and the poisson ratio parameters are defined as material properties. The material isa steel isotropic material. A total of mechanical and elastic stress analyzes were carried out under the constant load of25000 and 20000 kN applied to Fx, Fy, Fz beam axes and 2 MPa pressure on the 3D lattice roof model. Deformations of themodel against the load were investigated by analyzing the stresses against the mechanical forces and the elastic stresses inthe x, y, z axes. As a result of the analyses, it was observed that the mechanical and elastic stresses in the beam axes againstthe applied load increased.
Keywords: Mimarlık; İnşaat Mühendisliği